EVALUATION OF LEARNING AND TRAINING OF LANGUAGE: BY ROI EVALUATION MODEL - Aris Try Andreas Putra (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
Training is one of important requirements for the sustainability of aninstitution/organization. Some of the underlying reasons are the lack ofview and research results that show training which can increase valueaddedfor one and not only be an objective to affect short-termperformance. In addition, people in several countries, includingIndonesia believe that there is a positive correlation between trainingand education. Educational institutions also often choose training asone of the strategies to improve the quality of the performance ofteachers in the education personnel in order to achieve educationalgoals. One of the things that concern is and great for training programsare sometimes not followed by the evaluation of the effectiveness andtraining itself. Specifically, Kirkpatrick Keywords: Evaluation Model, Reaction, Learning, Behavior, Result andROI.